(untitled) (REMUNOM, 2025)
Aging is a natural and constant process that brings with it various morphophysiological changes, including sarcopenia, a geriatric syndrome characterized by the depletion of muscle mass in the elderly. This study sought to understand the process of losing lean mass and how it can be mitigated by increasing protein intake through whey protein supplementation, in order to improve the well-being of the elderly. An integrative literature review was carried out using articles published in PubMed, Scielo, Google Scholar, LILACS and Virtual Health Library (VHL) databases between 2000 and 2024. Studies on supplementation in the elderly population were selected. The progressive loss of muscle mass is due, among other factors, to a decrease in protein synthesis and an increase in degradation. The diagnosis of sarcopenia depends on nutritional and physical assessment, taking into account the parameters of strength, capacity and volume of muscle mass. According to studies, an increase in protein intake associated with physical exercise has a number of health benefits for the elderly, being able to increase muscle strength and thickness. It is concluded that whey protein is a viable alternative, since it is easily digestible and its composition contains amino acids of high biological value which help in protein anabolism and, consequently, improve the quality of life of the elderly.